Antitumor activity of intratumoral injection of pcDNA3.1-p27Kip1mt followed by in vivo electroporation in a malignant Burkitt’s lymphoma cell xenograft - Supriatno Supriatno; Sartari Entin Yuletnawati (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Human malignant Burkitt’s lymphomas are an uncommon type of Non-Hodgkin Lymphoma commonly affects in children. It is a highly aggressive type of B-cell lymphoma. Treatment for this malignant are still limited. However, a new strategy for refractory cancer, gene therapy is watched with keen interest. Recently, a novel method for high-efficiency and region-controlled in vivo gene transfer was developed by combining in vivo electroporation and plasmid cDNA. In the present study, a non-viral gene transfer system, in vivo electroporation in human malignant Burkitt’s lymphoma (Raji) cell xenograft was investigated. Purpose: The purpose of this study was to evaluate p27Kip1 gene therapy in Raji cell xenografts using pcDNA3.1-p27Kip1 mutant type (mt) and pcDNA3.1 empty vector (neo) with the local application of electric pulses. Methods: True experimental study using post-intervention with control group design was performed in this study. Material sample was obtained from integrated research laboratory at faculty of dentistry, Universitas Gadjah Mada, Yogyakarta. The efficiency of transfection of exogenous p27Kip1 gene by electroporation was confirmed by Western bloting analysis. To evaluate the reduction of malignant Burkitt’s lymphoma cell xenografts by this method, the volume of Raji cell xenografts in mice after electroporation with p27Kip1 mt or neo gene was measured. Results: Up-regulation of p27Kip1 protein was detected in pcDNA3.1-p27Kip1 mt. Furthermore, the growth of tumors was markedly suppressed by p27Kip1 mt gene transfection compared with transfection of neo. Conclusion: Injection of pcDNA3.1-p27Kip1 mt gene followed by in vivo electroporation has a high-potentially to suppress the growth of malignant Burkitt’s lymphoma cells. Furthermore, combination system of pcDNA3.1-p27Kip1 mt-injected tumor and electroporation might be used for human oral cancer. Latar belakang: Limfoma Burkitt’s maligna banyak terjadi pada anak-anak dan merupakan jenis yang langka dari limfoma NonHodgkin (NHL). Limfoma Burkitt’s maligna adalah tipe yang sangat agresif dari limfoma sel B. Perawatan penyakit ini masih sangatterbatas, walaupun demikian strategi baru perawatan kanker menggunakan terapi gen menjadi pusat perhatian. Suatu metode baru transfer gen untuk meningkatkan efisiensi dan kontrol area telah dikembangkan dengan mengkombinasi elektroporasi in vivo dan plasmid cDNA. Pada penelitian ini, telah diteliti sistim transfer gen non-virus dengan elektroporasi in vivo terhadap xenograft sel limfoma Burkitt’s maligna (sel Raji). Tujuan: Tujuan dari penelitian ini adalah untuk mengevaluasi terapi gen p27Kip1 terhadap xenograft sel Raji menggunakan pcDNA3.1-p27Kip1 mutant type (mt) dan pcDNA3.1 empty vector (neo) dengan aplikasi lokal elektroporasi. Metode: Jenis penelitian yang digunakan adalah eksperimen murni memakai rancangan pasca intervensi dengan kelompok kontrol. Sampel dan bahan penelitian didapat dari laboratorium riset terpadu, Fakultas Kedokteran Gigi, Universitas Gadjah Mada, Yogyakarta. Efisiensi transfeksi gen p27Kip1eksogen dengan elektroporasi dilakukan dengan analisis Western bloting. Untuk mengevaluasi hambatan xenograft sel limfoma Burkitt’s maligna dengan metode elektroporasi, dilakukan pengukuran volume xenograft sel Raji pada tikus pasca elektroporasi dan injeksi gen p27Kip1 mt atau neo. Hasil: Peningkatan regulasi protein p27Kip1 terdeteksi pada gen pcDNA3.1-p27Kip1 mt. Selanjutnya, pertumbuhan tumor secara signifikan terhambat oleh transfeksi gen p27Kip1 mt dibandingkan dengan transfeksi neo. Kesimpulan: Injeksi gen pcDNA3.1-p27Kip1 mt disertai elektroporasi in vivo mempunyai potensi yang kuat menghambat pertumbuhan "> sel limfoma Burkitt’s maligna. Kombinasi sistim injeksi tumor menggunakan gen pcDNA3.1-p27Kip1 mt dan elektroporasi kemungkinan dapat digunakan untuk terapi kanker oral.